2020
DOI: 10.1371/journal.pgen.1008605
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rare variants in circulating metabolic biomarkers

Abstract: Circulating metabolite levels are biomarkers for cardiovascular disease (CVD). Here we studied, association of rare variants and 226 serum lipoproteins, lipids and amino acids in 7,142 (discovery plus follow-up) healthy participants. We leveraged the information from multiple metabolite measurements on the same participants to improve discovery in rare variant association analyses for gene-based and gene-set tests by incorporating correlated metabolites as covariates in the validation stage. Gene-based analysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Comparison of our results to those from published studies that focused on rare variant aggregation testing of metabolite levels [14][15][16][17][18][19][20]24 (Methods) showed that 32 of the 73 identified unique genes (44%) had not been reported as significant in any of these studies. Moreover, 115 of all 192 detected gene-metabolite associations (60%) were novel (Supplementary Table 4).…”
Section: Identification and Properties Of 192 Significant Gene-metabo...mentioning
confidence: 51%
See 2 more Smart Citations
“…Comparison of our results to those from published studies that focused on rare variant aggregation testing of metabolite levels [14][15][16][17][18][19][20]24 (Methods) showed that 32 of the 73 identified unique genes (44%) had not been reported as significant in any of these studies. Moreover, 115 of all 192 detected gene-metabolite associations (60%) were novel (Supplementary Table 4).…”
Section: Identification and Properties Of 192 Significant Gene-metabo...mentioning
confidence: 51%
“…We compared our significant findings to the significant findings from eight published genetic studies of the plasma/serum or urine metabolome that focused on rare exonic variant aggregation testing and used sequencing and high-throughput metabolomics data [14][15][16][17][18][19][20]24 . We first assessed whether the genes identified in our study were reported as associated with any metabolite in any of the seven studies at their respective multiple-testing corrected significance threshold, after having mapped all gene names to their current version in Ensembl version 109 using https://www.ensembl.org/biomart/martview.…”
Section: Comparison To Previous Rare Variant Association Studies and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of gene-based studies using proteomics or other types of omics data have also been performed. For example, using WES data and a large set of metabolites, rare-variant associations were identified for five genes previously known to be associated with the same phenotypes 27 . Few gene-based studies have been performed with WGS data to discover associations with rare variants.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we integrate the QTL data with additional molecular QTL data derived from the same study (Figure 1). These data include plasma protein levels measured through an antibody-based proximity extension assay (Olink Target panels, n=4,662-4,981 individuals) 17,18 and an aptamer-based multiplex protein assay (SomaScan v3, n=3,301) 5 , as well as serum metabolite levels measured using an untargeted mass spectrometry platform (Metabolon HD4, n=14,296) 10 and a nuclear magnetic resonance spectroscopy platform (Nightingale Health, n=40,849) 19,20 .…”
Section: Introductionmentioning
confidence: 99%